Language learning strategies used by English language majors / Nur Nadtrah binti Naim - Naim, Nur Nadtrah (2015)
Various researches revealed language learners’ preferences on language learning strategies vary due to a few reasons. However, studies on how good language learners usually learn and practise the target language will provide new perspectives for the current trends and developments of language learning and teaching (Lightbown & Spada, 2006), especially among those majoring in English language. Thus, this small-scale study aims to investigate how the undergraduates majoring in English language and Linguistics at University of Malaya employ language learning strategies to enhance their English language efficiently. Quantitative and qualitative research designs were used to identify the learners’ preferences on types of strategies, frequency of usage and in what ways the preferred language learning strategies among the learners vary with their programme year of study. Using Oxford’s (1990) Strategy Inventory of Language Learning (SILL) Version 7, the quantitative data were analysed in the form of average scores and percentages. Categorization and thematic analysis were used to analyse the qualitative data retrieved from the interview. The findings revealed that majority of the learners prefer social and metacognitive strategies more than other types of language learning strategies. They were indeed frequent users of strategies and this finding also was reflected in their results of self-rating on proficiency level. The participants from each year of study were found to have similar patterns on the preferred types of strategies and how they go about learning the language. This research contributes perspectives about strategies in language learning and awareness about the effectiveness of using strategies that can be considered as pertinent to develop learners’ achievements in language learning as well as its implications toward the educators, syllabus designers and researchers.